Release of circulating tumor cells and cell-free nucleic acids is an infrequent event in synovial sarcoma: liquid biopsy analysis of 15 patients diagnosed with synovial sarcoma - Dóra Mihály; Noémi Nagy; Gergő Papp; Zsuzsanna Pápai; Zoltán Sápi (BMC, 2018)
Abstract Background Synovial sarcoma is a rare soft tissue tumor which contains the unique SS18-SSX1, SS18-SSX2 - or, rarely, SS18-SSX4 - fusion transcripts. It is well known that some soft tissue tumors, like Ewing sarcomas and myxoid liposarcomas, can spread via the blood with free circulating tumor cells (CTC); this can be detected by several sensitive molecular biology methods. Here we report a study of fifteen synovial sarcoma patients with varied clinical backgrounds. Method After blood withdrawal and nucleic acid isolation, we attempted to detect the SS18-SSX fusion genes from circulating tumor cells or cell-free nucleic acids with nested PCR and droplet digital PCR. Results SS18-SSX2 fusion transcript was identified in a small copy number with droplet digital PCR in one case. Nested PCR could not detect any of the fusion transcripts in the examined 15 synovial sarcoma cases. Conclusions Heretofore two case reports could detect CTCs in synovial sarcoma - in the first paper, the patient was diagnosed with poorly differentiated type while the other had a rare primary gastric synovial sarcoma. However, until now, no other studies have detected CTCs in the peripheral blood of synovial sarcoma patients. Based on our findings, we can conclude that detection of the chimeric SS18-SSX fusion gene after surgical excision and/or chemotherapy/radiotherapy is a rare circumstance and hence in itself is not sufficient for monitoring the tumor recurrence. Therefore, monitoring of other possible biomarkers - for example synovial sarcoma specific miRNAs - is recommended.